Faktor-Faktor yang Mempengaruhi Angka Kematian Akibat Kecelakaan Lalu Lintas di Sumatera Barat Menggunakan Analisis Jalur - Hadiyanti Riskha; Arnellis Arnellis; Yenni Kurniawati (UNIVERSITAS NEGERI PADANG, 2019)
Abstract – Traffic accidents are a problem that needs serious attention given the enormous losses incurred. West Sumatra is one of the provinces in Indonesia which has a fairly high accident rate. The problems of this study are the factors that influence significantly the mortality rate from traffic accidents in West Sumatra as well as how big the influence of these factors on the level of fatalities in West Sumatra. Data taken from the 2009-2012 in the Central Bureau of Statistics and West Sumatra police data. This research method using path analysis, a method that can analyze the factors that directly and indirectly to the death rate from traffic accidents. Factors that influence the mortality rate due to accidents directly is the number of accidents, while the factors that affect poverty indirectly the number of violations and the roads are damaged.Keywords – path analysis, accident, factors that affect accident.